PENERAPAN ETIKA BISNIS ISLAM DALAM TRANSAKSI JUAL BELI DARING DI TOKO ONLINE SHOPEE - Azizah, Mabarroh (Hukum dan Masyarakat Madani, 2020)
The practice of buying and selling online, a seller is required to be not deliberate contradiction between words and deeds in his business. The seller must have a mandate by displaying an attitude of openness, honesty, optimal service, and doing good with everything, let alone relating to community service. That there are some problems that occur in buying and selling online (online). Among these are sellers who post pictures on Shoppe that don't match the original. This study aims to explain the application of Islamic business ethics in Shopee's online store. This type of research is juridical-normative or normative legal research. the nature of this research is descriptive-analysis research. Primary data is research material in the form of rules, norms about Islamic business ethics and documented online trading concepts. Data collection techniques in this study used literature, documentation and interviews. Data analysis technique is done by inductive thinking. The results showed that: the application of Islamic business ethics in the practice of buying and selling online (online) at Shopee's online store, has not implemented Islamic business ethics. Because there are still lies and also post pictures that are not in accordance with the original.
Keywords: Business ethics; Buying and selling online